CO2 emissions embodied in bilateral trade in China: An input-output analysis - Unal, Emre; Lin, Boqiang; Managi, Shunsuke (Elsevier Science Inc, 2023)
The effects of export goods on CO2 emissions in China were calculated using input-output analysis via the hypothetical extraction method (HEM). The seven largest export partners of China were taken into account for the analysis: the US, Japan, South Korea, Germany, India, the UK and the Netherlands. First, using input-output analysis, the effects of CO2 emissions were allocated between the non-tradable goods, total export goods, exported final goods and exported intermediate goods sectors. Then, using a weighted multipliers approach, efficiency in CO2 emissions was allocated among the sectors. It was found that although non-tradable goods caused the highest CO2 emissions, export goods, especially intermediate goods showed the largest growth in emissions. In addition, export goods contributed more to emissions efficiency. Second, the HEM was implemented to explore which countries had significant effects on both emissions and emissions efficiency. The US was the largest source of CO2 emissions in China in terms of final goods. Nevertheless, the US also increased the role of exported intermediate goods on emissions. It was also an important country in stimulating efficiency in CO2 emissions. Hence, China does not have a chance to decrease its export performance against the countries such as the US, as their demand is the source of efficiency in CO2 emissions. However, it can focus on exported intermediate goods to mitigate emissions, and take the US into account for new policies.
Keywords: CO2 emissions; Hypothetical extraction method; Input-output analysis